Community knowledge and attitude towards Japanese encephalitis in Darrang, India: a cross-sectional study - Ahmad, Akram; Khan, Muhammad Umair; Malik, Sadiqa; Jamshed, Shazia Qasim; Gogoi, Lakhya Jyoti; Kalita, Manabendra; Sikdar, Atul Prasad (Medknow Publications, 2017)
Background: The prevalence of Japanese encephalitis (JE) in Assam was exceptional in a global context in the year 2014. Darrang district is amongst the most affected districts that is hit by deadly JE virus in Assam. Therefore, we conducted this study to evaluate the knowledge and attitudes of the residents regarding JE at Darrang. Methods: A descriptive, cross-sectional study was performed for the period of 3 months from November 2014 to January 2015 in Darrang. Multistage stage sampling was done to select participants from the district. A pretested interviewer-administered questionnaire was used to collect data from the participants. Descriptive analysis and logistic regression tests were used to analyze the data. Results: A total of 396 participants responded to the questionnaire, thus giving the response rate of 51.5%. One-fourth of the participants exhibited a good knowledge of JE (24.7%). The majority of the participants incorrectly answered the questions relating to management (83.3%) and prevention of JE (66.7%). Further, tertiary education and JE patient in family/relative were significantly associated with the knowledge of the participants (P < 0.001). A large proportion of the respondents exhibited positive attitudes towards JE (96.5%). Television was the major source of information of the participants regarding JE (29.2%). Conclusion: The findings of this study indicate a lack of knowledge regarding JE among the residents of Darrang. However, their attitudes towards JE were generally positive. Further studies on this topic need to be conducted throughout the state of Assam to identify and subsequently bridge the knowledge gaps among its residents